SCOPE OF OPERATIONS MANAGEMENT IN THE ERA OF INDUSTRY 4.0: IOT AND ERP TECHNOLOGY - Hery Purnomo; Subagyo; Faisol; Badrus Zaman; Poniran Yudho Leksono (Adisam Publisher, 2025)
This study aims to analyse the expansion of the scope of operations management in the Industry 4.0 era through the integration of Internet of Things (IoT) and Enterprise Resource Planning (ERP) technologies. This study uses a literature review research method. The results of the study show that IoT plays an important role in providing real-time data through sensors and connected devices to support machine condition monitoring, predictive maintenance, and supply chain optimisation, while ERP functions as an integrated system that processes operational big data into comprehensive managerial information for production planning, inventory control, and integrated inter-functional coordination. The integration of IoT and ERP has been proven to reduce downtime, lower operational costs, improve planning accuracy, and strengthen end-to-end visibility of operational processes, thereby driving a shift from reactive operations management to proactive and adaptive smart operations. These findings confirm that the synergistic use of IoT and ERP is a strategic prerequisite for organisations seeking to enhance their competitiveness and readiness for smart factories within the Industry 4.0 framework.